JULIAN, ULPIAN I NIETYPOWA POŻYCZKA. ZASTOSOWANIE ANALOGII W ROZWAŻANIACH PRAWNICZYCH - Kacprzak, Agnieszka (Zeszyty Prawnicze, 2016)
JULIAN, ULPIAN AND THE ATYPICAL LOAN: ON ANALOGY AS APPLIED IN LEGAL REASONING Summary The paper concerns the legal controversy as to the possibility of transforming a debt that is due under a contract of mandate or any other consensual contract into a loan by means of a bare agreement (pactum). Under such an agreement the creditor would entitle his debtor to keep the equivalent of the debt – which already existed between them – as a loan. The discussion took place between Julian, the eminent jurist of the midsecond-century A.D, and Ulpian, the jurist of the first half of the third century A.D. Julian argued against the possibility of classifying the contract in question as a loan. His arguments were based on analogy, distinction, and reductio ad absurdum (D.17,1,34 pr.). Ulpian, on the other hand, defended the possibility that was ruled out by his predecessor. Interestingly enough, the latter relies on analogy as his main argument as well. His conclusion is drawn, however, from analogy with the very same situation which Julian considered distinct from the case in question (D. 12,1,15). In the article, it is argued that this diversity of opinions can be explained by the different interpretations of the characteristic of the loan as a real contract. From Julian’s standpoint, this characteristic required the loan to be the title of acquisition by the borrower of ownership of money or things that are thereby considered the object of the loan: if the money or things were acquired on any other grounds, no loan could be construed (not to mention the case where the debtor does not – materially – acquire any money at all). Ulpian, on the other hand, was concerned not as much with the material substrate of the loan as with the economical calculus: in this perspective, indeed, the agreement – which tended to replace the hitherto debt by the loan-debt of the same amount – turned out to be a perfect substitution of a double payment, which would lead to the same effect. It is important to note one of the consequences to which Ulpian’s reasoning could lead: the possibility that someone who has never obtained any money from anyone or indeed never had them, nevertheless could be considered to have borrowed them (e.g. someone obliged to pay damages is entitled by the creditor to keep the amounts due as a loan of money that he never materially obtained). In order to accept this consequence, some serious redefinition of the concept of the loan as a real contract seems necessary, to say the least. The paper argues that – when ruling out the transformation – Julian strove to avoid accepting this very consequence.